KEPRIBADIAN, GAYA HIDUP, DAN KOMPENSASI SEBAGAI DETERMINAN KINERJA KARYAWAN - Yuyuk Liana; Firliany Ahlia Adenia; Darti Djuharni; Djoko Sugiono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
Research conducted on a coffee shop in Malang is intended to examine and analyze the influence of personality, lifestyle, and compensation on employee performance. Data were collected through questionnaires which were distributed to 59 respondents that consisted of managers and employees. Data were analyzed using multiple linear regression using SPSS. The results of this study indicate that personality has no significant effect on employee performance, lifestyle has a negative effect on employee performance, and compensation has a positive effect on employee performance. According to the partial test of each variable, compensation has the highest significant effect on employee performance since compensation is the primary motivation for employees to work to support their daily needs. Keywords: compensation, life style, performance, personality